2021
DOI: 10.1186/s12936-021-03760-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of artemether–lumefantrine and artesunate–amodiaquine for the treatment of uncomplicated Plasmodium falciparum malaria in Mali, 2015–2016

Abstract: Background The current first-line treatments for uncomplicated malaria recommended by the National Malaria Control Programme in Mali are artemether–lumefantrine (AL) and artesunate–amodiaquine (ASAQ). From 2015 to 2016, an in vivo study was carried out to assess the clinical and parasitological responses to AL and ASAQ in Sélingué, Mali. Methods Children between 6 and 59 months of age with uncomplicated Plasmodium falciparum infection and 2000–200,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…All three study sites demonstrated an AL efficacy of over the WHO threshold, with ACPRs in Agadez, Tessaoua, and Gaya of 97.05%, 98.87% and 92.18%, respectively. Several studies have evaluated the efficacy of AL in Niger and the sub region and have demonstrated its continued efficacy in West Africa: 91% efficacy in Sélingué, Mali in 2015 [ 20 ], 96.7% and 96.3% efficacy in Bohicon and Kandi, Benin, respectively, in 2018 [ 21 ], 98.8% efficacy in Kédougou, Senegal, in 2018 [ 22 ] and 98.8% efficacy in Abidjan, Côte d’Ivoire, in 2016 [ 23 ]. In addition to its efficacy, this molecule is well tolerated by patients and no adverse events were reported during the study.…”
Section: Discussionmentioning
confidence: 99%
“…All three study sites demonstrated an AL efficacy of over the WHO threshold, with ACPRs in Agadez, Tessaoua, and Gaya of 97.05%, 98.87% and 92.18%, respectively. Several studies have evaluated the efficacy of AL in Niger and the sub region and have demonstrated its continued efficacy in West Africa: 91% efficacy in Sélingué, Mali in 2015 [ 20 ], 96.7% and 96.3% efficacy in Bohicon and Kandi, Benin, respectively, in 2018 [ 21 ], 98.8% efficacy in Kédougou, Senegal, in 2018 [ 22 ] and 98.8% efficacy in Abidjan, Côte d’Ivoire, in 2016 [ 23 ]. In addition to its efficacy, this molecule is well tolerated by patients and no adverse events were reported during the study.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is similar to the CYP450s proteins, CYP6A14, and CYP6N6, which are involved in mosquito resistance by directly metabolizing deltamethrin. 4 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…Studies show that compared with past success in the Mali and Uganda regions of Africa, mosquito-borne infectious disease prevention and control programs have come to a standstill; even with the use of strengthened pesticides, malaria incidence is not decreasing any further but is, in fact, showing a trend of increase. 3 5 Therefore, research into the mechanism of mosquito resistance is vital to carry out an effective resistance program. Mosquito resistance emerges from the selection of adaptive insecticides involving multiple genes.…”
Section: Introductionmentioning
confidence: 99%
“…It remains a signi cant global health concern particularly in sub-Saharan Africa [1]. Central to antimalarial strategies are artemisinin-based combination therapies (ACTs), with artemether-lumefantrine standing out for its widely recognized e cacy in treating uncomplicated P. falciparum malaria [2][3][4]. The unique mechanism of action of ACTs involves rapid clearance of circulating parasites with artemisinin, coupled with the sustained action of the partner drug, making this combination a key component in the global malaria control toolkit.…”
Section: Introductionmentioning
confidence: 99%